Peranan Investasi Industri Kecil Menengah Dalam Penyerapan Tenaga Kerja Di Propinsi Sulawesi Utara - Parasan, Pradipta Mandasari; Tooy, Stephanie Mervin; Ombuh, Irvandy W; Roring, Gaby D J (Jurnal Ilmiah Raflesia Akuntansi, 2024)
Small and medium industries play an important role in the economy, especially in the local economy, in creating jobs. This can be done through investment flowing into small and medium industries, encouraging companies to open new business units, and, of course, having an impact on labor absorption, which means that investment in this field can also help regions overcome unemployment. Therefore, this study aims to see the role of small and medium industry investment on labor absorption in North Sulawesi Province, namely, the effect of SME investment on labor absorption. The data used in the study are secondary data, namely small and medium industry investment data and labor data in North Sulawesi Province, taken from the Central Statistics Agency (BPS) of North Sulawesi Province and then analyzed using the simple linear regression method using the Eviews 12 tool. The results of the study show that small and medium industry investment has a positive and significant effect on labor absorption in North Sulawesi Province. This certainly provides an illustration that the small and medium industry investment climate provides a good contribution to the absorption of labor. This means helping regions overcome unemployment. The results of this study are expected to help contribute to subsequent research related to the role of small and medium industry investment in labor absorption and also provide input to the government as a policymaker.